CRIMES AGAINST HUMANITY AND RESISTANCE IN LAKSMI PAMUNTJAK’S THE QUESTION OF RED - PUTRI ANGGRAENI (LITERA KULTURA : Journal of Literary and Cultural Studies, 2015)
Abstract This thesis employs Rome Statute of the International Criminal Court’s prominent concepts of crimes against humanity to describe the government and the military’s crimes against humanity in Laksmi Pamuntjak’s The Question of Red. Through the concepts of crimes against humanity, this thesis finds the government and the military’s crimes against humanity act to the civilian that is suspected as communist members. Further, the acts become part of the government authority and power. Almost all crimes against humanity acts depicted variously, from murder, extermination, torture, to apartheid. Such in Foucault’s studies, crimes against humanity as power drags out of resistance of the communist and almost all suspected civilian. The communist characters do not only appear personally, but also in organization or group of Buru Island prisoners. The resistances toward crimes against humanity are revealed into Hollander and Einwohner’s eight type of resistance. The typology of resistance is formed by three dimension of actor, target, and observer. Those dimensions are served in novel The Question of Red. Library method is appropriate to because this thesis datum are derived by close reading and analyzing intrinsic and extrinsic elements. Indeed, the references are taken in library and internet to support the analysis process. Further, this thesis is not served in numbering or table. Keywords: crimes against humanity, resistance, bourgeoisie, communist